ANALYSIS OF LEADERSHIP STYLES ON EDUCATIONAL MANAGEMENT AT PONDOK MODERN DARUSSALAM GONTOR - Zaki, Muhammad; Ashari, Riza; Ali Ridho, Arsyad Muhammad (Pascasarjana Unviersitas Majalengka, 2024)
This study analyzes various leadership styles' impact on educational management at Pondok Modern Darussalam Gontor. The research aims to explore how transformational and transactional leadership styles influence educational outcomes in this unique Islamic boarding school setting. Employing a qualitative descriptive approach, data were gathered through in-depth interviews and observations of school leaders, teachers, and students. Findings indicate that transformational leadership fosters a supportive and innovative learning environment, enhancing motivation and academic performance. In contrast, transactional leadership focuses on maintaining discipline and achieving short-term goals. The study highlights the critical role of adaptive leadership in managing educational processes effectively. Overall, effective leadership styles significantly shape educational management practices and contribute to achieving institutional goals in educational settings like Pondok Modern Darussalam Gontor.